Biodegradable spacer reduces the subacromial pressure: A biomechanical cadaver study. (February 2018) - Chevalier, Yan; Pietschmann, Matthias F.; Thorwächter, Christoph; Chechik, Ofir; Adar, Eliyahu; Dekel, Assaf; Müller, Peter E.
Abstract: Background: Failure after rotator cuff repair remains a major clinical problem and could be related to excessive pressures from the acromion. Previous studies with irreparable tears showed good clinical results of tendon healing with arthroscopic insertion of a protective biodegradable spacer balloon between the repaired tendon and the acromion. One hypothesis is that compression pressures on the repaired tendon will be reduced by the spacer. This cadaver study aimed to investigate the effects of this subacromial spacer on compression pressures over a repaired supraspinatus tendon in passive motion. Methods: Rotator cuff tear and repair were performed in six fresh-frozen cadaveric shoulders, followed by insertion of a biodegradable subacromial spacer. Specimens were tested using a passive shoulder simulator for abduction-adduction, flexion-extension and internal-external rotations. A sensor positioned below the acromion was used to measure compression pressure changes through passive range of motion before and after placement of a subacromial spacer. Peak pressures were measured in adduction-abduction motion, near 90° abduction. Findings: Both the mean and peak pressures in abduction-adduction were significantly reduced after insertion of the subacromial spacer (from mean 121.7 (SD 9.5) MPa to 51.5 (SD 1.2) MPa and from peak 1749.6 (SD 80.7) MPa to 535.1 (SD 27.6) MPa) (P < 0.0001). Interpretation: The reduced peak pressures and wider load distributions over the sensor during both passive abduction-adduction and flexion-extension motions suggest that the use of the spacer will lead to reduced wear of the repair in patients, and potentially prevent rotator cuff re-tear after surgical repair. Highlights: Subacromial pressure on rotator cuff tendon was measured in moving shoulder samples. This pressure is reduced when a compliant spacer lies between tendon and acromion. This spacer should reduce wear of the repair and prevent rotator cuff re-tears.